2017
DOI: 10.1590/1980-5918.030.001.ao18
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of patients with heart disease after cardiopulmonary rehabilitation program: case report

Abstract: Introduction: Recovery and maintenance of patients suffering from heart and respiratory diseases using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A significant increase was observed in the distance covered (375 to 420 meters). In another study, Fabrin et al 21 evaluated a COPD patient and found a significant improvement in the distance covered (345 to 490 meters) when the values of a 5-month pre-and postcardiopulmonary rehabilitation values were compared.…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase was observed in the distance covered (375 to 420 meters). In another study, Fabrin et al 21 evaluated a COPD patient and found a significant improvement in the distance covered (345 to 490 meters) when the values of a 5-month pre-and postcardiopulmonary rehabilitation values were compared.…”
Section: Discussionmentioning
confidence: 99%